2006
DOI: 10.1016/j.stam.2006.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen permeation through perovskite membranes and the improvement of oxygen flux by surface modification

Abstract: BSCF hollow fiber membranes possessing an asymmetric layered structure were prepared using a modified phase inversion process followed by subsequent sintering at temperatures from 1100 to 1175 1C. The fibers were characterized by SEM, and tested for air separation at ambient pressure and temperatures between 650 and 950 1C. Although the prepared hollow fibers resulted in self-supported asymmetric substrate with a very thin densified perovskite layer for mixed conduction, O 2 permeation was controlled by surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 10 publications
0
14
2
Order By: Relevance
“…We further demonstrate that catalytic surface modification of BSCF hollow fibres yields significant results, contrary to the quite modest improvements of up to 0.5 ml min −1 cm −2 of additional oxygen flux reported elsewhere for Pt [29] and Ag [30] catalysts. Effective surface modification is an important challenge for thin perovskite membranes (<1 mm thick) as any further reduction in thickness does not increase oxygen flux due to rate limitations in the oxygen surface dissociation/association reaction [31].…”
Section: Resultscontrasting
confidence: 81%
“…We further demonstrate that catalytic surface modification of BSCF hollow fibres yields significant results, contrary to the quite modest improvements of up to 0.5 ml min −1 cm −2 of additional oxygen flux reported elsewhere for Pt [29] and Ag [30] catalysts. Effective surface modification is an important challenge for thin perovskite membranes (<1 mm thick) as any further reduction in thickness does not increase oxygen flux due to rate limitations in the oxygen surface dissociation/association reaction [31].…”
Section: Resultscontrasting
confidence: 81%
“…Silver paste has been used by Wang et al [26], which found a "small" (unspecified) leakage at high temperature, and by Leo et al [27], who claim gas tightness verified by the absence of N 2 gas in the permeate. It is worth mentioning here that the absence of feed gas traces (N 2 ) on the permeate side does not (completely) prove gas-tightness conditions, as will be discussed later in this work.…”
Section: The Sealing System and Proceduresmentioning
confidence: 99%
“…Several studies have shown that surface modification leads to an improved surface exchange rate and a corresponding increase in the J O 2 . da Costa et al increased the J O 2 obtained with a BSCF hollow fibre after surface modification using noble metals [11,30]. The application of a porous layer made of a compatible material can also be considered as a way of increasing the area available for the surface exchange reactions [31][32][33][34][35].…”
Section: Influence Of Catalytic Layermentioning
confidence: 99%